2012
DOI: 10.1103/physrevb.85.205101
|View full text |Cite
|
Sign up to set email alerts
|

Nonreciprocal active metamaterials

Abstract: We show experimentally that active electromagnetic metamaterials are suitable for the implementation of a large class of non-reciprocal media characterized by magneto-electric constitutive parameters that cannot be achieved in passive materials. We design, fabricate and characterize an isolator made of such an active metamaterial slab and show that it is essentially transparent to microwaves propagating in one direction and opaque in the opposite direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…3, 4 The tailored microstructure of such metamaterials has to be much smaller than the wavelength, and this makes it very challenging to realize the desired magnetic properties for optical frequencies. Even though several studies have made approximations to ideal cloaking [5][6][7][8] and all-dielectric carpet cloaking has been demonstrated, 9 nobody has systematically addressed the intriguing question: "How efficiently can we cloak when using conventional simple isotropic dielectric media readily available in nature? "…”
Section: Topology Optimized Low-contrast All-dielectric Optical Cloakmentioning
confidence: 99%
“…3, 4 The tailored microstructure of such metamaterials has to be much smaller than the wavelength, and this makes it very challenging to realize the desired magnetic properties for optical frequencies. Even though several studies have made approximations to ideal cloaking [5][6][7][8] and all-dielectric carpet cloaking has been demonstrated, 9 nobody has systematically addressed the intriguing question: "How efficiently can we cloak when using conventional simple isotropic dielectric media readily available in nature? "…”
Section: Topology Optimized Low-contrast All-dielectric Optical Cloakmentioning
confidence: 99%
“…Metamaterial concepts have been shown to provide the right platform for the design of non-reciprocal electromagnetic media 22 . In this article, we nontrivially extend this methodology to acoustics, and describe a design approach that results in structures highly subwavelength, but strongly non-reciprocal for their size.…”
mentioning
confidence: 99%
“…Though there is some omega coupling present in the proposed unit cell, as evidenced by the Bloch impedance changing slightly with the propagation direction, it is very weak. In other suggested realizations ( [3,5,8]), the effect of other bianisotropic coupling phenomena (chiral coupling, omega coupling) is much more prominent. It was shown that the velocity parameter V can be varied without affecting the effective refractive index of the medium by simply changing the coupling between two inductors.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, our model when considering a finite slab corresponds, in fact, to a medium which is moving, but its boundaries remain stationary, similar to the movement of a conveyor belt (the other side of which is hidden from view). Obviously, this is also the case for any artificial realization of moving media lacking nonlinear elements or materials (e.g., [3,5,8]). …”
Section: Proposed Unit Cellmentioning
confidence: 98%